2013
DOI: 10.1074/jbc.m112.407684
|View full text |Cite
|
Sign up to set email alerts
|

UNC93B1 and Nucleic Acid-sensing Toll-like Receptors Mediate Host Resistance to Infection with Leishmania major

Abstract: Background: MyD88 is a critical element for host resistance to L. major. Results: UNC93B1 mutant and triple TLR3/7/9 knock-out mice are highly susceptible to infection with L. major. Conclusion: Nucleic acid-sensing TLRs are key sensors for Leishmania parasites. Significance: We disclose the mechanism by which L. major initiates IL-12 production and mediates development of Th1 lymphocytes and host resistance to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
5
31
0
1
Order By: Relevance
“…This shift could reflect changes in the cell types that principally mediate immune responses at different times in infection (discussed further below) or alternatively could be due to differential production or availability of TLR7 and TLR9 ligands by the parasite. Similar to our findings, other studies of bacterial and parasitic pathogens have found roles for multiple TLRs in sensing infection (66)(67)(68)(69). However, a seldom-addressed aspect of innate sensing that is highlighted by our study is that individual sensors can contribute to immune activation to various degrees during different stages of infection.…”
Section: Discussionsupporting
confidence: 78%
“…This shift could reflect changes in the cell types that principally mediate immune responses at different times in infection (discussed further below) or alternatively could be due to differential production or availability of TLR7 and TLR9 ligands by the parasite. Similar to our findings, other studies of bacterial and parasitic pathogens have found roles for multiple TLRs in sensing infection (66)(67)(68)(69). However, a seldom-addressed aspect of innate sensing that is highlighted by our study is that individual sensors can contribute to immune activation to various degrees during different stages of infection.…”
Section: Discussionsupporting
confidence: 78%
“…There are several studies that support a role for TLR-9 in sensing L. major infection [106, 112–114]. TLR-9 deficiency in mice results in an enhanced T H 2 response, and only transiently inhibits the development of a T H 1 response and parasite clearance, as these mice are eventually able to heal their cutaneous lesions after L. major and L. brasiliensis infection [106, 112, 113, 115, 116]. Also, similar to TLR-9 −/− mice TLR-7 −/− mice are slightly more susceptible to L. major infection, but TLR-3 −/− mice are resistant to infection [115].…”
Section: Tlr Activation In Leishmania Infectionmentioning
confidence: 99%
“…TLR-9 deficiency in mice results in an enhanced T H 2 response, and only transiently inhibits the development of a T H 1 response and parasite clearance, as these mice are eventually able to heal their cutaneous lesions after L. major and L. brasiliensis infection [106, 112, 113, 115, 116]. Also, similar to TLR-9 −/− mice TLR-7 −/− mice are slightly more susceptible to L. major infection, but TLR-3 −/− mice are resistant to infection [115]. Infection of TLR-7/9 and TLR-3/7/9 knockout mice with L. major indicated that these mice were more susceptible to infection then single-gene deficient mice.…”
Section: Tlr Activation In Leishmania Infectionmentioning
confidence: 99%
“…Apart from its specificity for DNA, TLR9 has been shown to directly recognize hemozoin, an insoluble crystalline byproduct generated by Plasmodium falciparum during the process of detoxification after host hemoglobin is digested (Coban et al 2010). Additionally, TLR3, TLR7, TLR9, and UNC93B1 render host resistance to Leishmania major infection (Schamber-Reis et al 2013).…”
Section: Cd11bmentioning
confidence: 99%